2012
DOI: 10.1038/ng.2350
|View full text |Cite
|
Sign up to set email alerts
|

The Blk pathway functions as a tumor suppressor in chronic myeloid leukemia stem cells

Abstract: A therapeutic strategy for treating cancer is to target and eradicate cancer stem cells (CSCs) without harming their normal stem cell counterparts. The success of this approach relies on identification of molecular pathways that selectively regulate CSC function. Using BCR-ABL-induced chronic myeloid leukemia (CML) as a disease model for CSCs, we show that BCR-ABL down-regulates the B lymphoid kinase ( Blk ) gene through c-Myc in leukemia stem cells (LSCs) in CML m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 59 publications
0
62
0
Order By: Relevance
“…Patient samples consisted of leukapheresis products taken at the time of diagnosis of chronic-phase CML, and written informed consent was obtained in accordance with Declaration of Helsinki principles and with IRB approval from the National Health Service Greater Glasgow. CML mice were treated with PD146176 in vitro in a colony-forming assay; also, CML mice were treated with PD146176, and then BM cells were isolated for analysis in the colony-forming assay, which was carried out as previously described (48).…”
Section: Cd38mentioning
confidence: 99%
“…Patient samples consisted of leukapheresis products taken at the time of diagnosis of chronic-phase CML, and written informed consent was obtained in accordance with Declaration of Helsinki principles and with IRB approval from the National Health Service Greater Glasgow. CML mice were treated with PD146176 in vitro in a colony-forming assay; also, CML mice were treated with PD146176, and then BM cells were isolated for analysis in the colony-forming assay, which was carried out as previously described (48).…”
Section: Cd38mentioning
confidence: 99%
“…Inhibition of this Blk pathway accelerates CML development, whereas increased activity of the Blk pathway causes the delay of CML development. Importantly, we showed that Blk is dispensable for normal hematopoiesis (Zhang et al, 2012c). Our data demonstrated that Blk regulation in LSCs of CML is independent of BCR-ABL kinase activity, and this pathway plays a critical role in regulating the survival of CML LSCs.…”
Section: The Hypoxia Inducible Factor Pathwaymentioning
confidence: 76%
“…HIF1a -/-LSCs gave rise to less colonies in vitro and failed to induce CML in the secondary recipients (Zhang et al, 2012b) (Texido et al, 2000); however, combined deficiency of the three Src kinase, Blk, Fyn, and Lyn, impairs pre-B cell receptor mediated NF-kB activation, and results in blocking of B cell development (Saijo et al, 2003). Recently, we found that Blk plays an inhibitory role in BCR-ABL-induced CML (Zhang et al, 2012c). Deletion of Blk accelerates CML development; conversely, overexpression of Blk suppresses the development of CML through its inhibitory effects on the function of LSCs.…”
Section: The Hypoxia Inducible Factor Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Although increasing evidence demonstrated that CML stem cells utilize signaling pathways that are independent of BCR-ABL kinase activity for their maintenance and survival [11,12], the underlying molecular mechanisms remain unclear. To address these challenging issues, we performed a DNA microarray assay to compare the gene expression profiles between LSCs and normal HSCs.…”
Section: Introductionmentioning
confidence: 99%